Domestication of Blue Swimming Crab for Sustainability: Growth and Genetic Change - Andi Aliah Hidayan, Yushinta Fujaya; Tassakka, Asmi Citra Malina A.R.; Kalsum, Umi (European Journal of Sustainable Development, 2019)
Blue swimming crabs (Portunus pelagicus) are a fisheries resource which is currently threatened by over-exploitation. Crab culture is one approach which can contribute towards sustainable use of blue swimming crab (BSC) populations. In this context, BSC domestication is considered necessary. The purpose of this study was to evaluate the genetic and growth changes occurring during initial stages of a BSC domestication program. The DNA of selected strains was examined using Random Amplified Polymorphism DNA (RAPD). Five OPA primers were used to generate a fragment pattern from the samples collected. The RAPD results showed that BSC domestication combined with selection for fast growth resulted in genetic change, with a genetic distance of 0.1053 – 0.3158 between 1st and 4th generations. This distance was associated with significantly higher growth rates after the 4th generation. After 100 days grow-out, mean growth in carapace width was 103 mm for 1st generation crabs and 109 mm in the 4th generation, with respective growth rates of 1.0 mm/day and 1.1 mm/ day. Domestication with selection of fast growing individuals as BSC broodstock resulted in a positive shift towards DNA characteristics associated with faster growth in subsequent BSC generations. Keywords: Blue swimming crab, Sustainability, Domestication, Selective breeding, Growth rate, RAPD